IMPROVING FISHERMEN'S WELFARE THROUGH ACCESS TO MICROFINANCE: AN ANALYSIS FROM A FINANCIAL LITERACY PERSPECTIVE - Nurul Yusyawiru; Jaya Dwi Nurcholis; Putri Yuliandari; Mutiara Maulina Arzakiyah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Research Aims: This study aims to evaluate and scrutinize the overall efficacy of financial inclusion initiatives, specifically microfinance programs and financing decisions, in improving the welfare of fishermen. The focus of this study is on the role of behavior, knowledge, and financial stability in increasing the assessing the transformative outcomes of financial integration and financing decisions on fishermen's welfare. Design/methodology/approach: This study used a population of fishermen in the Riau Islands who utilize microfinance programs. Adopting a quantitative approach, this research utilized survey-based methods to gather data from 150 participants. These individuals were selected through a purposive sampling strategy, and the resulting data were processed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via the SmartPLS application. Research Findings: This research proves that financial literacy significantly improves financial inclusion and the quality of funding decisions. In addition, financial behavior and stability have been shown to encourage financial inclusion, although financial stability actually reduces fishermen's dependence on external debt. Overall, financial inclusion and appropriate funding decisions are key determinants in improving the welfare of fishermen Theoretical Contribution/Originality: This research differentiates itself through the development of a holistic model that uniquely integrates financial literacy, behavior, and stability into one unified framework to comprehensively explain the welfare of fishers. The specific focus on maritime communities in the Riau Islands gives it an advantage over other general research because it is able to formulate contextual solutions to the erratic fishermen's income cycle